Review articleImportance of inflammation leading to cardiovascular events in diabetes - Prokopczuk, Przemysław; Wawrusiewicz-Kurylonek, Natalia; Kinalska, Ida (Przegląd Kardiodiabetologiczny/Cardio-Diabetological Review, 2006)
Chronic inflammation plays a key role in the process of atherosclerosis and its complications; also many publications show that inflammation is involved in pathogenesis of type 2 diabetes and is responsible for occurrence of cardiovascular events in these patients. Metabolic disturbances characteristic for diabetes such as hyperglycaemia, dyslipidaemia or insulin resistance may intensify the ongoing inflammation as well as be a result of chronic inflammation. Markers of chronic inflammation such as CRP or IL-6 can serve as predictors of cardiovascular complications. Further trials are needed to work out effective methods of treatment which would limit the risk of cardiovascular events.